2004
DOI: 10.1111/j.1365-2249.2005.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

The bisphosphonate acute phase response: rapid and copious production of proinflammatory cytokines by peripheral blood gd T cells in response to aminobisphosphonates is inhibited by statins

Abstract: SummaryThe bisphosphonates are a novel class of drug that have been registered for various clinical applications worldwide. Bisphosphonates, and in particular the aminobisphosphonates (nBPs), are known to have a number of sideeffects including a rise in body temperature and accompanying flu-like symptoms that resemble a typical acute phase response. The mechanism for this response has been partially elucidated and appears to be associated with the release of tumour necrosis factor (TNF)a a a a and interleukin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(159 citation statements)
references
References 87 publications
(137 reference statements)
4
150
1
4
Order By: Relevance
“…It was more probably linked to local 17 mucosal inflammation and bone necrosis, thus being the consequence of the induction of osteoclast differentiation and 18 activity, due to the increased RANKL/OPG ratio. IL-6 is considered to be an osteoclastogenic cytokine, and thus an isopentenyl pyrophosphate, which is a potent activator of human peripheral blood γδ T cells [28]. Moreover, this latter 23 study found a correlation between the mevalonate pathway and γδ T cell activation by statin administration: statins 24 inhibited the activation of human peripheral blood γδ T cells in response to endogenous non-sterol mevalonate products.…”
mentioning
confidence: 81%
“…It was more probably linked to local 17 mucosal inflammation and bone necrosis, thus being the consequence of the induction of osteoclast differentiation and 18 activity, due to the increased RANKL/OPG ratio. IL-6 is considered to be an osteoclastogenic cytokine, and thus an isopentenyl pyrophosphate, which is a potent activator of human peripheral blood γδ T cells [28]. Moreover, this latter 23 study found a correlation between the mevalonate pathway and γδ T cell activation by statin administration: statins 24 inhibited the activation of human peripheral blood γδ T cells in response to endogenous non-sterol mevalonate products.…”
mentioning
confidence: 81%
“…This threshold might be used for implementing preventing strategies for APR, for example, based on the administration of statins in conjunction with aminobisphosphonates. (13) It is known that both the risk of APR (12) and the number and proportion of gd T cells decreases with aging. (14,15) However, we found that also the age-adjusted gd T cell number and proportion remain significant determinants of the occurrence of APR.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study has demonstrated that zoledronate did not reduce the population of osteoclast precursor after 18 months of treatment in osteopenic women, (27) There are also conflicting in vitro data regarding the effect of bisphosphonates on osteoclastogenic cytokines such as IL-1, TNF and circulating levels of RANKL and osteoprotegerin (OPG) (28)(29)(30)(31)). RANKL is produced by the osteoblasts and binds to the receptor RANK which is located on the osteoclast precursor cells as well as the mature osteoclast (32).…”
Section: Introductionmentioning
confidence: 97%